Is privatization of education beneficial for Morocco? : evaluation of Morocco's privatization policy on the basis of a cross-sectional study of quality of education in public and private schools in Casablanca - Abbad Elandaloussi, Zineb (2016)
The aim of this thesis was to evaluate Morocco’s privatization policy based on the opinions of final-year high-school students (n = 103) that were studying in either public or private schools. This was examined using a cross-sectional study design in which a structured, Likert scale questionnaire was administered at a night school in Casablanca, Morocco, where highschool students can take extra classes in preparation for their final year exam. The results were analyzed quantitatively by comparing the group means with an independent samples ttest, using an alpha level of 0.05. The results of the study indicated that socioeconomic status was significantly higher for students studying in private schools. There were some significant differences in items related to school environment, policy environment and effectiveness of teaching with one item favoring private schools and two items favoring public schools. However, there were no significant differences between public and private schools in items regarding equality, home and community environment and cultural contexts. Considering the significant results were slightly in favor of public schools and that threequarters of the averages were higher for public school students, it appears that the quality of education may be similar for both public and private schools in Morocco. However, due to this study having been conducted in just one school in Casablanca and the fact that student satisfaction was the only measure of quality of education, the results should be interpreted cautiously. However, this raises the concern that more information is needed to draw reliable conclusions about whether Morocco should continue with the current aggressive privatization policy of education. For now, the policy of increasing privatization in Morocco and other lowincome countries should be reconsidered until more is known about its impact on quality and equality of education.